2021
DOI: 10.5005/jp-journals-10005-1944
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Efficacy of Triple Antibiotic Paste and Propolis as an Intracanal Medicament in Young Permanent Teeth: An In Vivo Study

Abstract: A bstract Aim and objective To evaluate the antimicrobial efficacy of triple antibiotic paste and propolis extracts as an intracanal medicament in young permanent teeth. Materials and methods A total of 30 single-rooted non-vital young permanent teeth with open apex were selected randomly from the children aged between 7 years and 14 years with no systemic complications. Group I—triple antibiotic paste and group II be propolis allocating 15 te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Scrapping the dentin surface was done to have samples from deeper dentin levels. Paper points were used to absorb the transport fluid with dentin chips formed (15,29,30) .…”
Section: Discussionmentioning
confidence: 99%
“…Scrapping the dentin surface was done to have samples from deeper dentin levels. Paper points were used to absorb the transport fluid with dentin chips formed (15,29,30) .…”
Section: Discussionmentioning
confidence: 99%
“…Within the clinical applications of propolis, it is possible to mention the anticaries and microbial effect against oral pathogens [43]. Lillygrace et al [82] identified, from a randomized clinical trial, antimicrobial activity in dental treatment with intracanal application, with a reduction similar to the known conventional treatment.…”
Section: Other Assaysmentioning
confidence: 99%
“…Some studies showed significant increases in SCAP proliferation, while others showed no change in cytotoxicity depending on the concentration [8][9][10]. Propolis, a natural resin produced by honeybees, was shown to be significantly less cytotoxic than calcium hydroxide [14], while exhibiting antibacterial efficacy similar to that of TAP and calcium hydroxide [15][16][17], with additional antiviral, anti-inflammatory, and antioxidant properties [18]. Although propolis has good biocompatibility and antimicrobial effects, which makes it a good candidate for a natural intracanal medicament, it should be used with caution in vivo because of its allergenic potential [19].…”
Section: Introductionmentioning
confidence: 99%